Preparing Supporting Infrastructure for Destination Branding: A Study of Geotourism Pioneering in Ulubelu Lampung - Eli Jamilah Mihardja (International Journal of Geotourism Science and Development, 2023)
Ulubelu sub-district has geotourism potential that can be developed to support the improvement of local community welfare. Combined with the tourism potential of coffee plantations, Bakrie University developed the Coffee Geotourism Program with Pertamina Geothermal Energi Ulubelu area in the Kedaireka 2022 Matching Fund program. This program includes designing a site plan to later become part of the Ulubelu Geothermal Village destination branding strategy. Data were collected from July to December 2022 through in-depth interviews with residents and village officials, observation, and literature study. The results of the research were compiled as a draft site plan that includes mapping and visibility planning to support destination branding.